Analysis of the Achievement of Sustainable Development Goals (SDGs) Target without Poverty in Riau Province - Alfina Safira Zahra; Yusni Maulida; Taryono Taryono (Indonesian Journal of Economics, Social, and Humanities, 2026)
This study aims to analyze the completion of criteria and schemes related to the Sustainable Development Goals (SDGs) without any poverty. Poverty is a condition that describes a household, community, or individual who is in a condition of deprivation, particularly in fulfilling basic needs. This might result in inequality and injustice within the economic structure. In order to achieve the objective of ending poverty by 2030, all stakeholders are striving to implement various policies, programs, and activities to fulfill the target determined for Riau Province of 5.86%. This includes poverty eradication, the implementation of social safety, the fulfillment of economic resources and access to basic services, reducing community vulnerability to disasters, as well as strengthening policies and mobilizing various resources to eliminate existing poverty. The poverty rate in rural areas has consistently been higher than in urban areas over the past 10 years, although the gap has been decreasing. This study uses secondary data obtained from the Central Statistics Agency and the Regional Development Planning Agency of Riau Province. The method used is the BaU scenario method, which consists of forecasting, trends, and scenario design using Microsoft Excel. The results of the study show that the government has not been able to achieve zero poverty in Riau Province. Regarding the implementation of sociodemographic management programs, residential development programs, and ecological disaster management programs, all have successfully exceeded the outlined targets, but enhancements are required to exceed the targets that have been set. For the implementation of empowerment programs, improving household welfare, potable water services, access to basic sanitation services, and health facility access programs, the targets have not been achieved, and additional effort is required to implement the programs to exceed the set targets.